Agent-based flow control for HLA components - Zhao, Zhiming (2013)
Human-in-the-loop simulation systems, also called interactive simulation systems (ISSs), play an increasingly important role in problem-solving environments for complex problems. The High Level Architecture (HLA) provides a uniform interface for realizing the interoperability between distributed modules and has been widely applied in the construction of ISSs. However, using the current architecture, control of the simulation logic and activity flows is often fused with interconnection details, and the constituent components of an ISS have limited adaptability for other applications for which they would, in principle, be suited. An agent-based architecture, named the Interactive Simulation System Conductor (ISS-Conductor), is developed on top of the HLA. It provides a separate layer for describing, interpreting, and controlling activity flow between the HLA components. Using the ISS-Conductor architecture, a simulation or an interactive visualization system is encapsulated as a component, which contains an agent for invoking the simulation and visualization activities and an agent for controlling the runtime behavior.